A cooperação brasileira em educação : estudantes convênio dos Países Africanos de Língua Oficial Portuguesa - Silva, Áurea Gardeni Sousa da (2015)
The main objective of this study was to learn more about the experience of students from the Países Africanos de Língua Portuguesa (African Countries of Portuguese Official Language) – PALOP, at UNB and UFMT, in the cities of Brasília-DF and Cuiaba-MT, and the process through which they enter the Brazilian Instituições de Ensino Superior (Higher Education Institutions) – IES. These students’ entry to Brazilian universities is via the Programa Estudante de Convênio de Gradução (Graduate Covenant Student Program) – PEC G. This program is part of the cooperation in education, included in the larger context of the Cooperação Técnica entre Países em Desenvolvimento (Technical Cooperation among Developing Countries) – Brazilian CTPD. The CTPD is one of the main instruments of Brazilian relationship with the PALOP countries. In this context, historical and cultural ties, Portuguese language and solidarity are used as arguments for the strengthening of relations between Brazil and these countries. Given this context, it has become relevant to research the PALOP students’ experience in Brazil. Considering the proposed aims and the research problem, we opted for the qualitative research and in-depth interviews as the main data collection technique. The work also led to some participant observation experience and required researching the Pró-Reitoria de Assistência Estudantil (Dean of Students Assistance) – PRAE-UFMT files about the PEC G, as well as researching the official publications of the Ministério da Educação (Ministry of Education) – MEC, Ministério das Relações Exteriores (Ministry of Foreign Affairs) – MRE, the Agência Brasileira de Cooperação (Brazilian Cooperation Agency) – ABC, all available on their official websites on the Internet. The permanence of PALOP students in Brazil is unfolded in at least two main perspectives, namely: foreign university students are inserted in a context devoid of proper infrastructure to receive them; and, as the research showed, there are situations of discrimination and racism that such students undergo daily, for being African and black. The research demonstrates two main relevant factors: the narrative of the main difficulties faced by PALOP students and the strategies that such students use to establish themselves and to dwell in the universities and cities where they live, given the absence of official support, not provided by the PEC G.